Simplified Protocol for the Purification of Native Cas Nucleases for DNA-Free Genome Editing - Margherita D’Amico; Flavia Angela Maria Maggiolini; Lucia Rosaria Forleo; Maria Francesca Cardone; Riccardo Velasco; Teodora Basile; Carlo Bergamini (Methods and Protocols)
DNA-free genome editing by the direct delivery of CRISPR-associated nucleases has emerged as a promising technology due to its precision and reduced risk of off-target effects. However, existing purification protocols for native Cas proteins require the use of complex instrumentation, which limits their application. Here, we present a simplified protocol for the purification of native Cas9, Cas12RR and dCas9-VP64 nucleases optimized for DNA-free genome editing. Our approach leverages a streamlined affinity and ion exchange chromatography coupled with minimal downstream processing, ensuring a good yield and activity of the purified proteins. The in vitro analysis of the purified ribonucleoprotein complex demonstrated a good efficiency of DNA target cleavage. This simplified protocol increases the opportunity to adopt CRISPR technology, and enables broader access to DNA-free genome editing tools also for laboratories that are not specifically equipped for protein purification.